The Use of Code Mixing in Nessie Judge’s YouTube Channel Video: NERROR True Crimes - Ida Ayu Gde Atlantika Putri Arkuri; Putu Devi Maharani (Austronesian: Journal of Language Science & Literature, 2023)
Nowadays, the ability to use two languages ​​in communication is an interesting phenomenon because it involves some language mixing, also known as code mixing. This study describes the types of code mixing and the reason for code mixing in Nessie Judge’s YouTube channel videos, using theory from Hoffman (1991). This study adopts a qualitative descriptive method. There are six videos from Nessie Judge’s YouTube channel, from May 2018 to August 2021, were chosen for data analysis. There are four steps in the data collection process. The first is finding Nessie Judge’s YouTube channel, the second is watching her videos, the third is taking note of the phrase Nessie used that contained code mixing, and the fourth step is classifying the data regarding the causes and forms of code mixing. The results show that two types: intra-sentential and intra-lexical. However, for the type involved, the writers did not find a change in pronunciation. As for the reasons, only three were found: talking about a particular topic, repetition used for clarification, and the intention of clarifying the speech content for the interlocutors. Besides that, the dominant data found is the intra-sentential type, with a total of 52 data, and the dominant reason used is talking about a particular topic, with a total of 45 data. It is anticipated that this work will advance and build a theoretical viewpoint on linguistics, particularly in the research of code-mixing. Additionally, this research may aid in sociolinguistic advancement, particularly in language studies and theories.